The Problematization of Mining in Argentina: A Study of the Provinces of Jujuy and San Juan - Godfrid, Julieta (2024)
This article analyzes the construction of mining as a public issue in Argentina and its impact on the institutional framework of the mining sector. From a qualitative approach, two subnational states that promote mining are analyzed: the Provinces of Jujuy and San Juan. In the context of socioenvironmental conflicts, mining has been questioned which pressured subnational states to introduce institutional changes. The analysis focus on the repertoires of collective action of local populations, the construction of networks of actors for the visibility of the problem, as well as the moral and cognitive factors that influenced the problematization of mining in Argentina.